1982
DOI: 10.1128/aem.43.2.357-361.1982
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Properties of a Malolactic Enzyme from a Strain of Leuconostoc mesenteroides Isolated from Grapes

Abstract: An enzymatic complex able to transform L-malate to L-lactate was obtained from a Leuconostoc mesenteroides strain isolated from grapes. The molecular weight was about 235,000, the isoelectric point was at pH 4.35, and the optimal pH for activity was 5.75. The malolactic activity followed a sequential pattern concerning the involved substrates. At pH values substantially different from the optimum, a positive cooperativity between malate molecules was observed. Oxamate, fructose-i,6-diphosphate, and L-lactate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1

Year Published

1988
1988
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(42 citation statements)
references
References 5 publications
1
40
1
Order By: Relevance
“…This confirmed that SO 2 production by yeast strains was negligible. Neither were there any differences in suc-cinate and tartrate contents (0.1-0.15 and 2.0-2.5 g l À1 , respectively), both inhibitors of MLF [25]. The concentrations of acetate at the end of MLF were between 0.1 and 0.2 g l À1 in any case, an acceptable and usual value.…”
Section: Other Analytical Parameters Of Winesmentioning
confidence: 75%
“…This confirmed that SO 2 production by yeast strains was negligible. Neither were there any differences in suc-cinate and tartrate contents (0.1-0.15 and 2.0-2.5 g l À1 , respectively), both inhibitors of MLF [25]. The concentrations of acetate at the end of MLF were between 0.1 and 0.2 g l À1 in any case, an acceptable and usual value.…”
Section: Other Analytical Parameters Of Winesmentioning
confidence: 75%
“…Protein concentration was determined with the BCA protein assay reagent (Pierce). MLE activity was determined at 37°C by measuring the CO 2 released from L-malate with a specific CO 2 electrode (Eischeweiler and Co) [3]. The specific activity was expressed as micromoles of CO 2 released per minute per milligram of protein.…”
Section: Preparation Of Cell-free Extracts and Measurement Of Enzymatmentioning
confidence: 99%
“…The specific activity was expressed as micromoles of CO 2 released per minute per milligram of protein. LDH activity (pyruvate to lactate) was performed as described elsewhere [3]. L-Malate and L-lactate were determined by enzymatic methods (Boehringer Mannheim).…”
Section: Preparation Of Cell-free Extracts and Measurement Of Enzymatmentioning
confidence: 99%
See 2 more Smart Citations